(untitled) (Applied Biological Research, 2019)
The present study was aimed to analyze molecular diversity of submergence tolerant genotypes of rice. Thirty four SSR primers were used to generate allelic variants (4 alleles in RM 23843 and 27 in RM 23662). Altogether 410 allelic variants were detected at 42 SSR loci with a mean of 9.76 alleles per locus. Analysis of divergence pattern based on SSR markers allowed differentiation and classification of rice varieties into 8 clusters. A large range of similarity coefficient revealed by SSR markers provided greater confidence for the assessment ofgenetic divergence and interrelationship among the submergence tolerant rice genotypes. A perusal of similarity coefficients reflected a very high degree of similarity between rice genotypes ‘Anh Hsung Seln’ (C 11) and ‘Hsung Teing’, whereas ‘FR 13A’ and ‘Swarna Sub-1’ were more diverse for breeding programme to generate more recombinants. Use of SSR markers appeared more efficient in achieving unique and unambiguous characterization and differentiation of varieties used in the present study. The SSR analysis also revealed unique or variety specific allele which could be useful as DNA fingerprints in the identification and preservation of different genotype and to develop highly submergence tolerance varieties.